Designing a Tourism Minibus Driver Chair by Using IDEAS Framework in a Virtual Environment - Lintangsari, Putri Suci; Yuliawati, Evi; Suroso, Hastawati Chrisna (2477 - 6165, 2020)
Indonesia is a high tourism sector country which provides opportunities for tour and travel service business. Thereby increasing the growth rate of accidents by 3.3%, one of which was caused by buses. Hafizh 58 Jaya, a company in the field of tourism services, had many complaints against drivers about the problem of muscle disorders due to the lack of ergonomic position of the driver or the seat used which was not suitable with the user or not ergonomic. To analyse this problem, IDEAS framework was applied. This method could describe overall minibus driver movement and produce designs that were appropriate with the level of risk on small musculoskeletal disorders. By normal driving activity, the second driver had the largest PEI parameter index value, 2,186. It was categorized as medium to low-risk musculoskeletal disorders. This meant that the actual chair with normal driving activity was not optimal and not ergonomic. The final design of the redesign chair has given optimal and ergonomic results shown by highest PEI index parameter value of 1,336. This PEI index parameter was categorized at the low risk of musculoskeletal disorders.